THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND EQUITY ACTIVITIES ON CUSTOMER RESPONSE Study at the Pudu Sentral Hotel, Kuala Lumpur, Malaysia - Ai Sri Kusmayanti; Vina Oktaviana; Gugyh Susandy (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
Brand equity currently plays an important role for the company so that the brand created can convey its value to potential customers. And social media marketing is currently one of the media promotion tools for companies to improve and build their target market. The purpose of this study was to determine the effect of social media marketing and brand equity on customer responses. With hypothesis testing. The study population was 155 people with a sample of 113 respondents. The results of this study indicate that the social media marketing activity variable (X1) to the customer response variable (Y) has no positive effect. This is evidenced by testing the hypothesis by using the T test that produces a calculated T value smaller than T Table, namely the value of T 1,930 <t table 1.98. So H1 is rejected and Ho is accepted. So SMMA (X1) does not contribute to customer response (Y). While the brand equity variable (X2) has a positive effect on the customer response variable (Y). This is evidenced by testing the hypothesis by using the T test that produces a calculated T value greater than T table that is a calculated value of 7.728> 1.98. So H1 is accepted and Ho is rejected. So Brand Equity (X2) has a contribution to customer response (Y).